MicroRNA 8059 as a marker for the presence and extent of coronary artery calcification. Issue 1 (31st January 2018) - Howlett, Philippa; Cleal, Jane K; Wu, Huihai; Shah, Nikunj; Horton, Alex; Curzen, Nick; Mahmoudi, Michael
Abstract : Objective: MicroRNAs (miRNAs) may serve as potential biomarkers in a variety of pathologies. The aim of this study was to determine whether miRNAs could serve as blood-based markers of isolated coronary artery calcification (CAC) defined as CAC in the absence of an underlying metabolic abnormality. Methods: 24 age-matched and sex-matched patients who had been referred for elective CT coronary calcium score and angiography as part of investigation for cardiac chest pain were recruited. Peripheral venesection was performed and an Agatston calcium score was derived from the CT coronary angiogram using default software. RNA was extracted using the LeukoLOCK Total RNA Isolation System for Toray's microarray analysis and quantitative reverse transcription PCR (qRT-PCR). Results: The patients were well matched for age, sex and conventional risk factors for coronary artery disease. Microarray analysis identified lower expression of miRNA-138-2-3p, miRNA-1181, miRNA-6816-3p and miRNA-8059 in patients with coronary artery calcium score (CACS)=0 vs CACS>100. qRT-PCR confirmed significant downregulation of miRNA-8059 in patients with CACS>100 (CACS=0 vs CACS>100; P=0.03). Conclusion: miRNA-8059 may serve as a peripheral blood-based biomarker for the presence of CAC, as well as provide a platform for studying the pathophysiological basis of isolated CAC. Trial registration number: NCT01992848; Results.